Cyclical unemployment, structural unemployment - Peter Diamond (Federal Reserve Bank of Boston, 2013)
Whenever unemployment stays high for an extended period, it is common to see analyses, statements, and rebuttals about the extent to which the high unemployment is structural, not cyclical. This essay views the Beveridge curve pattern of unemployment and vacancy rates and the related matching function as proxies for the functioning of the labor market and explores issues in that proxy relationship that complicate such analyses. Also discussed is the concept of mismatch.
Keywords: E24; E32; E6; J23; 330; Konjunkturelle Arbeitslosigkeit; Strukturelle Arbeitslosigkeit; Beveridge-Kurve; Arbeitsmarkt; Matching; Theorie; USA